EMOTIONAL FREEDOM TECHNIQUES DAPAT PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI - Teti; Subiyanto, Paulus (MEDIA ILMU KESEHATAN, 2013)
Background: Hypertension is a condition when the systolic blood pressure over 120 mmHg and diastolic blood pressure was more than 80 mmHg. Untreated hypertension will lead to complications such as stroke, coronary heart disease, narrowing of blood vessels, kidney failure, heart failure and diabetes mellitus can even cause death. There by preventing these complications do one non-pharmacological therapy is by using the Emotional Freedom Technique. Objective: Knowing there any influence of emotional freedom techniques to decrease blood pressure in people with hypertension. Methods: This research was aquasi-experimental. Sampling using purposive sampling with the number of respondents 30 people were divided into two groups: an intervention group(n =15) andcontrol group (n=15). Interventions carried 6 times for 2 week session. The statistical test used is Paired t-test and Independent t-test with significance level Î±=0.05. The results: The results of this study indicate that patients with hypertension in the intervention group had a mean value of 21.33 mmHg lower post test than the pretest value, whereas in the control group had a mean value of 7.33 mmHg decrease from pretest value. Results Paired sample t-test obtained p value =0.000 (p <0.005). Then Ho is rejected and Ha accepted. Mean while, according totest result sobtained by the Independent t-test t value=-6.212 (p =0.000) can be concluded there is a significant difference between the decrease in average blood pressure between emotional freedom technique intervention group and the control group. Conclusion: Emotional Freedom Technique has influence in lowering blood pressure in people with hypertension are significant compared with the control group without the Emotional Freedom Technique. Keywords: Emotional Freedom Technique, Blood Pressure, Hypertension.